Analysis of economic growth through strengthening zakat contributions with the analytic network process (ANP) approach - Nurul Badriyah; Setyo Tri Wahyudi; Kartika Sari; Amalia Rahmawati; Fajrin Intan Safitri; Radeetha Radeetha; Fadillah Putra; Agung Pramana Warih Marhendra (Journal of Innovation in Business and Economics, 2025)
This study discusses the strengthening of cooperation and institutions in optimizing zakat management, with a case study on LAZISNU Malang City using the Analytic Network Process method. The results show that applicability to institutions has the most significant influence (weight 0.43966), emphasizing the importance of relevant and effective policies to support zakat institutions. LAZISNU Malang City has been actively establishing strategic cooperation with various parties, including Islamic financial institutions and local governments, to increase zakat collection. Regulation also plays an important role in strengthening the zakat management structure (weight 0.30071) with a positive impact on the efficiency of zakat distribution and the acceleration of its distribution to mustahik. The aspect of the speed of zakat distribution (weight 0.25604) is a critical element, especially in emergency situations, ensuring that the benefits of zakat are immediately felt by the community. In addition, adequate zakat literacy (weight 0.204) has been proven to support the active participation of muzakki, as found in various empirical studies. This study confirms that strengthening cooperation, implementing effective regulations, increasing literacy, and adopting technology are strategic steps to optimize zakat as a socio-economic instrument in Malang City.